Community-Based Child Trauma Recovery Strategies After Flash Floods in Aceh Tamiang–Langkat - Kamalia Kamalia; Annisa Arrumaisyah Daulay; Muhammad Putra Dinata Saragi; Dika Sahputra; Muhammad Saffuan Abdullah (Jurnal IPTEK Bagi Masyarakat, 2026)
Flash floods cause not only physical damage but also psychological impacts on children as a vulnerable group. Although various post-disaster trauma recovery programs have been developed, community service studies that integrate child psychosocial intervention, parental involvement, and local volunteer capacity building within a community-based recovery model remain limited. This community service program aimed to implement a community-based trauma recovery strategy for children affected by flash floods in the Aceh Tamiang–Langkat region. The program involved 35 children aged 6–12 years who were directly affected by the disaster. A participatory approach was applied through initial assessment, psychosocial intervention, psychoeducation, and pre-post intervention evaluation. Data were collected using a simple psychosocial observation sheet covering indicators of anxiety, emotional expression, social interaction, sense of safety, and child participation, supported by brief interviews with parents and local volunteers. The data were analyzed descriptively by comparing children’s conditions before and after the intervention. The intervention consisted of play therapy, drawing, storytelling, collaborative games, and structured group activities. The results showed that 74% of children experienced reduced anxiety, 80% demonstrated improved emotional expression, and 77% showed increased social interaction. In addition, the involvement of parents and local volunteers strengthened social support and contributed to program sustainability. These findings indicate that community-based trauma recovery can serve as a relevant, practical, and sustainable psychosocial intervention model for addressing children’s psychological needs in post-disaster contexts.